Cleaner remediation of antibiotic wastewater: From efficient photocatalytic degradation to reduced ecological risk via Cd-doped Bi2MoO6/Bi5O7I S-scheme heterojunction coupled with interfacial engineering - Yingjie Liu; Hui Peng; Ji Ma; Yufang Su; Zhenfeng Lin; Chunling Liu; Yongfu Guo (Journal of Environmental Sciences, 2026)

Potent sucrase inhibition by purple sweet potato anthocyanins for glycemic control: unveiling peonidin-3-caffeoyl-feruloylsophoroside-5-glucoside as the key functional monomer and its interaction mechanism - Jing Li; Yushan Wang; Luyao Wang; Zhenfeng Yue; Binqiao Sun; Siqi Lin; Si Li; Guiyun Chen; Luelue Huang (Food Chemistry, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

Innovative S-scheme heterojunction of Cu-doped BiVO4 integrated with BiOI for simultaneous antibiotic degradation and algal inactivation: DFT insights and applications - Yinxiang Hao; Mingyue Shao; Ji Ma; Yufang Su; Zhenfeng Lin; Yongfu Guo (Journal of Environmental Sciences, 2026)

Response of soil humic substances to snowpack decline across different soil layers in the subalpine forest - Li Zhang; Wenlan Huang; Yao Liu; Sining Liu; Han Li; Bo Tan; Chengming You; Hongwei Xu; Lin Xu; Zhenfeng Xu; Yalin Yuan; Jiao Li; et al. (CATENA, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Corrigendum to “In vitro/vivo evaluation of novel mitochondrial targeting charge-reversal polysaccharide-based antitumor nanoparticle” [Carbohydrate Polymers Volume 234 (2020) 115930] - Lei Fang; Hua Lin; Zhenfeng Wu; Zhen Wang; Xinxin Fan; Ziting Cheng; Xiaoya Hou; Daquan Chen (Carbohydrate Polymers, 2026)

Patterns and drivers of plant- and microbial-derived carbon in a cedar plantation chronosequence of subtropical China - Yuehan Wang; Yu Li; Chengming You; Hongwei Xu; Han Li; Lin Xu; Li Zhang; Lixia Wang; Sining Liu; Bo Tan; Yaling Yuan; Jiao Li; et al. (Plant and Soil, 2026)

Superenhancer-driven SMC4 promotes myeloma growth by epigenetically enhancing IFI16-dependent STING signaling - Jiayun Guan; Xuanyi Lin; Zhenfeng Dai; Jianbiao Zhou; Zhen Cai; Tze King Tan; Tae-Hoon Chung; Xiaochen Zhang; Wee-Joo Chng; Xiaoxiang Rong; Yunlu Jia (Apoptosis, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Changes in litter chemical properties mediate the effects of soil arthropods on the microbial community during litter decomposition in a subalpine forest - Aomiao Wu; Jingru Liu; Rui Yin; Lin Xu; Chengming You; Zhenfeng Xu; Li Zhang; Han Li; Lixia Wang; Sining Liu; Hongwei Xu; Bo Tan (Applied Soil Ecology, 2026)

Fiscalin B exerts an anticancer effect through mitochondria-modulated apoptosis and cell cycle arrest in human hepatocellular carcinoma - Siqi Wang; Yi Huang; Songtao Wang; Hao Gong; Qingqin He; Dingmeng Zhang; Zhenfeng Fang; Le Zhou; Kuan Lin; Yongxiang Song (Natural Product Research, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

Data augmentation-based fault diagnosis framework for nuclear power plants with robust anti-data interference capability - Jiangkuan Li; Shangcai Zheng; Jiaoshen Xu; Meng Lin; Zhenfeng Niu; Jiahao Cheng; Chenxin Zhu; Ruifeng Tian; Sichao Tan (Annals of Nuclear Energy, 2025)

Spatial confinement-enabled full-color emission from carbon dots via controlled sp2 domain assembly in spray pyrolysis - Lin Lan; Zhenfeng Gan; Yuan Ma; Rui Bao; Xin Kong; Liang Liu; Jianhong Yi (Chemical Engineering Journal, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Enhanced oil recovery through CO2 injection: The role of pentane in improving miscibility of CO2 and oil - Mingwei Zhao; Yuxin Xie; Xiangjuan Meng; Lin Li; Caili Dai; Zhihao Zhang; Zhenfeng Ma; Yingnan Wang; Zhongzheng Xu; Xuguang Song (Fuel, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Porous g-C3N4 nanosheets modified walnut-like Bi4O5I2 for efficient degradation of antibiotic under visible light: DFT calculations, mechanism and practical application - Yuxiang Xu; Zihan Chen; Ji Ma; Guoying Zhu; Zhenfeng Lin; Jingtao Shen; Yongfu Guo (Journal of Water Process Engineering, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Intelligent control of ginger far-infrared radiation and hot-air drying based on multi-sensor fusion technology - Yongsheng Pei; Lin Fan; Changzhi Wang; Guizhong Tian; Xiangyi Meng; Zhenfeng Li; Wanxiu Xu (Food and Bioproducts Processing, 2025)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

Evaluation of black tea appearance quality using a segmentation-based feature extraction method - Feihu Song; Xiaolong Lu; Yiqing Lin; Qiaoyi Zhou; Zhenfeng Li; Caijin Ling; Chunfang Song (Food Bioscience, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Insight into functional groups of salt compounds on the performance of viscoelastic surfactant-based fluids - Xiangyu Wang; Zhengjian Hou; Mingwei Zhao; Xuhao Wang; Peng Liu; Xufeng Lin; Zizhao Wang; Zhenfeng Ma; Caili Dai (Fuel, 2024)

Warming effects on C:N:P stoichiometry and nutrient limitation in terrestrial ecosystems - Hongwei Xu; Minggang Wang; Chengming You; Bo Tan; Lin Xu; Han Li; Li Zhang; Lixia Wang; Sining Liu; Guirong Hou; Yang Liu; Zhenfeng Xu; et al. (Soil and Tillage Research, 2024)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Effects of livestock grazing on the relationships between soil microbial community and soil carbon in grassland ecosystems - Hongwei Xu; Chengming You; Bo Tan; Lin Xu; Yang Liu; Minggang Wang; Zhenfeng Xu; Jordi Sardans; Josep Peñuelas (Science of The Total Environment, 2023)

The utilization of physically based models and GIS techniques for comprehensive risk assessment of storm surge: A case study of Huizhou - Si Wang; Lin Mu; Hao Qin; Lizhe Wang; Zhenfeng Yao; Enjin Zhao (Frontiers in Marine Science, 2022)
Quantitative analyses of storm surge risk, which are mostly focused on physical vulnerability, have been widely used to help coastal communities mitigate impacts and damage. Such assessments, however, overlook the social aspect of vulnerability in storm surge risk. By considering both the community’s social vulnerability and buildings’ physical vulnerability, this study proposed a methodology that incorporates social vulnerability into the framework for making quantitative risk assessments of storm surge using a coupled hydrodynamic and wave model, Geographical Information System (GIS) techniques, and the Principal Component Analysis (PCA) method. The coastal area of Huizhou was chosen as the case study due to its high concentration of oil and gas infrastructure in China’s southern Guangdong Province. By combining hazard, exposure, physical vulnerability, and social vulnerability, it was possible to explore the effect of social vulnerability on the physical vulnerability-based risk assessment of storm surge and determine the overall risk level. First, the Gumbel distribution was utilized to establish five representative and plausible hypothetical typhoon events with different return periods (10, 20, 50, 100, and 1000 years) for the study area. Then, using the well-validated fully-coupled model, the Simulating Waves Nearshore (SWAN) model and the ADvanced CIRCulation (ADCIRC) model, storm surge simulations for defined return periods were run, and the geographical distribution of the maximum surge elevations displayed on a GIS platform was used to assess hazard levels. In terms of the physical aspect, the depth-damage functions for buildings were established to estimate direct economic losses and assign risk levels accordingly. For the social vulnerability of a community, a composite score was computed using the PCA method by combining and aggregating indicators representing various characteristics of the social group. The results show that the overall risk level, taking into account both social vulnerability and physical vulnerability, has decreased on average. It suggests that social vulnerability-based risk assessment may account for a significant portion of the overall risk assessment, which is frequently overlooked in traditional storm surge risk assessment. Additionally, the comprehensive and precise risk maps can assist local policymakers in identifying areas at different risk levels and developing evacuation plans, thereby minimizing potential losses, especially in high-risk areas.

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Preparation and characterization of dissolving hyaluronic acid composite microneedles loaded micelles for delivery of curcumin - Ziting Cheng; Hua Lin; Zhen Wang; Xiaoyu Yang; Mei Zhang; Xuechun Liu; Bingjie Wang; Zhenfeng Wu; Daquan Chen (Drug Delivery and Translational Research, 2020)